Research on cloud-based traffic adaptive command and control method for mobile botnet - Wei CHEN; Shi-wen ZHOU; Cheng-yu YIN (Tongxin xuebao, 2014)
Botnet is a serious attack evolved from traditional malwares.With the rapid development of computing capability and mobile Internet access technology，building a realistic mobile botnet has become a potential threat.An adaptive traffic control mechanism for cloud-based mobile botnet was proposed.It adopts different traffic consumption strategies according to different 3G or Wi-Fi network environments.Then scheduling algorithms to execute botnet commands was applied.The experimental results show the traffic adaptive algorithm can improve the stealthy and efficiency of mobile botnet while ensure that the botnet commands can be executed effectively.